Candidates for Balancing Selection in Leishmania donovani Complex Parasites. (2nd December 2021) - Grace, Cooper Alastair; Forrester, Sarah; Silva, Vladimir Costa; Carvalho, Kátia Silene Sousa; Kilford, Hannah; Chew, Yen Peng; James, Sally; Costa, Dorcas L; Mottram, Jeremy C; Costa, Carlos C H N; Jeffares, Daniel C
Abstract: The Leishmania donovani species complex is the causative agent of visceral leishmaniasis, which cause 20–40, 000 fatalities a year. Here, we conduct a screen for balancing selection in this species complex. We used 384 publicly available L. donovani and L. infantum genomes, and sequence 93 isolates of L. infantum from Brazil to describe the global diversity of this species complex. We identify five genetically distinct populations that are sufficiently represented by genomic data to search for signatures of selection. We find that signals of balancing selection are generally not shared between populations, consistent with transient adaptive events, rather than long-term balancing selection. We then apply multiple diversity metrics to identify candidate genes with robust signatures of balancing selection, identifying a curated set of 24 genes with robust signatures. These include zeta toxin, nodulin-like, and flagellum attachment proteins. This study highlights the extent of genetic divergence between L. donovani complex parasites and provides genes for further study.